The parsec-scale structure, kinematics, and polarization of radio-loud narrow-line Seyfert 1 galaxies. Issue Volume 10:Issue S313(2014) (24th March 2015) - Richards, J. L.; Lister, M. L.; Savolainen, T.; Homan, D. C.; Kadler, M.; Hovatta, T.; Readhead, A. C. S.; Arshakian, T. G.; Chavushyan, V.
Abstract: Several narrow-line Seyfert 1 galaxies (NLS1s) have now been detected in gamma rays, providing firm evidence that at least some of this class of active galactic nuclei (AGN) produce relativistic jets. The presence of jets in NLS1s is surprising, as these sources are typified by comparatively small black hole masses and near- or super-Eddington accretion rates. This challenges the current understanding of the conditions necessary for jet production. Comparing the properties of the jets in NLS1s with those in more familiar jetted systems is thus essential to improve jet production models. We present early results from our campaign to monitor the kinematics and polarization of the parsec-scale jets in a sample of 15 NLS1s through multifrequency observations with the Very Long Baseline Array. These observations are complemented by fast-cadence 15 GHz monitoring with the Owens Valley Radio Observatory 40 m telescope and optical spectroscopic monitoring with with the 2 m class telescope at the Guillermo Haro Astrophysics Observatory in Cananea, Mexico.